Visitation patterns of African elephants (Loxodonta africana) to a rubbish dumpsite in Victoria Falls, Zimbabwe - Jake Le Breton (Pachyderm)
Habitual crop raiding by elephants is a common cause of human–elephant conflict (HEC). While habitual raiding of rubbish dump sites by elephants is not be a typical case of HEC, it could be seen as a more indirect, passive form of conflict, caused by humans, which negatively affects both elephants and, potentially, humans. In 2016 several African elephants (Loxodonta africana) were found dead in a municipal dumpsite outside Victoria Falls, Zimbabwe. Others were observed consuming non-biodegradable waste from the site. In order to determine if the problem of dumpsite raiding by these wild elephants could be considered as an instance of HEC, we investigated the visitation patterns of elephants to the dumpsite and examined the presence of non-biodegradable waste in elephant dung found in the area. The results show that there was a clear trend in visitation patterns. A core group of up to 27 bull elephants habitually entered the site on a daily basis and spent several hours consuming waste from the dumpsite and drinking from the nearby sewage stabilization ponds between the early and late evening. A majority of elephant dung samples in the vicinity (71.6%) contained plastic waste. We discuss the potential negative effects this raiding has on the ecosystem and elephant health, and its potential contribution to HEC.